SOCIO-ECONOMIC DETERMINANTS OF HEALTH OUTCOMES IN THE SADC REGION - Damiyano, David; Dorasamy, Nirmala (International Journal of Psychosocial Rehabilitation, 2020)
The outcomes of health are influenced by many diverse factors, which range from socio-economic to health systems and environmental issues. This study will focus on health outcomes being represented by life expectancy. There are quite a few theoretical models that describe the health determinants concerning the outcomes, including the Wilber and Grossman models. In this study, the health indicators considered are total health expenditures, antiretroviral coverage, and improved water source. The study considers 11 of the 16 SADC countries using panel data for the period 2000-2015 from the World Bank for the study. Health outcomes were proxied by life expectancy from birth and current health expenditure per capita (US). Antiretroviral coverage as a percentage of people living with HIV as well as an improved water source as a percentage of the population were considered as independent variables. A unit change in current health expenditure per capita results in a 0.099162 positive change in life expectancy at birth. An increase in coverage for those people living with HIV will result in reduced deaths, increased quality of life, and hence a raising up of the life expectancy. Improved water supply source is statistically significant but is negative, which is inconsistent with literature.